Efficacy of phospho-vermicompost, biofertilizer, biopesticides and their integration against root rot of lentil - Farthouse, J; Hasna, M K; Khalil, M I; Haque, M M; Nabi, M K E; Haque, M A (Bangladesh Journal of Nuclear Agriculture, 2025)
Lentil is a valuable leguminous crop with high nutritional content, but it is susceptible to various soil-borne pathogens, including root rot, which can severely impact its yield and quality. In pursuit of sustainable and environmentally friendly agricultural practice, this study aimed to evaluate the efficacy of BINA phosphor-vermicompost, Biofertilizer BINA-LT-17 (Rhizobium leguminosarum), BINA biofungicide (Trichoderma asperellum), and their integration in managing root rot of lentil under field condition. Results from the study demonstrated that the application of phosphor- vermicompost (2 ton/kg) during final land preparation, seed coating with Biofertilizer BINA-LT-17(peat soil-based Rhizobium leguminosarum) and soil application of chickpea bran based BINA biofungicide (Trichoderma asperellum) significantly reduced root rot incidence while enhancing plant vigor and yield. This integrated approach demonstrated a synergistic effect, suggesting that combining organic amendments with beneficial microorganisms, including both Rhizobium and Trichoderma, can provide a comprehensive strategy to control root rot in lentil. Bangladesh J. Nuclear Agric, 38(2): 65-80, 2024